Final year project logbook portal - Murshida, Abdullah Kamil (2019)
Final Year Project (FYP) Logbook Portal is a Web-based application developed for Universiti Malaysia Pahang (UMP) communities which are students, supervisors, and coordinator that involved in the Final Year Project. This system is designed to replace the manual logbook of Final Year Project. Students claimed that it is difficult using the manual logbook because they did not understand their supervisor handwriting, forgot to bring the logbook during the meeting which is resulted the progress is made not meets the supervisor’s expectation. The main purpose of this project is to develop an online logbook as a replacement of the manual logbook of Final Year Project that can help the student progressing the Final Year Project become more productive. The system convenience for coordinator, supervisor and student who take the FYP. Its help the coordinator and supervisor to monitor the student progress on the Final Year Project. In order to develop the system, the Rapid Application Development (RAD) Methodology is used to manage the development process. This methodology can improve the quality of the project flow. This project incorporates some of the latest technology which using Bootstrap as graphic interface design, Visual Studio to develop the codes and PHPMyAdmin as the database storage. In conclusion, the Final Year Project (FYP) Logbook Portal connects both supervisor and student in order to make the progress of Final Year Project more efficient.